The use of Domino Learning Model to Improve Political Sociology Learning Motivation In PPKN FKIP UNRI - Erlinda, Sri (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to improve, know and describe the motivation to learn Political Sociology in the FKIP UNRIPPKn Study Program by using the Domino learning model. The research subjects were 36 semester V students consisting of 8 men and 28 women. The implementation of this learning improvement process was carried out in 2 cycles which were assessed by an observer. While the type of data is lecturer activity and learning motivation collected through observation sheets and questionnaires. After data is collected, grouped and analyzed based on descriptive methods. The results showed that the use of the Domino learning model could increase the motivation to learn Political Sociology in the FKIP UNRIPPKn Study Program.